Implementasi Sistem Pengelolaan Dana Sosial Dalam Meningkatkan Kesejahteraan Di Baitul Maal As’Adiyah Wonomulyo - Asia, Nur; Anwar, Nurfiah; Wardy Putra, Trisno (State of Islamic Institute Langsa, 2023)
This study aims to determine how the implementation of the social fund management system in the welfare of the community in Baitul Mal As'adiyah Wonomulyo. This article is included in field research with a qualitative approach. The methodology used is descriptive analysis studies and case studies. The results of the study concluded that the existence of Baitul Maal As'adiyah has a role and benefits in helping to improve micro, small and medium enterprises in the vicinity, namely by collecting Zakat, Infaq, and Shodaqoh funds from the community and then distributed to 8 asnaf and those who are entitled to receive them in the context of poverty alleviation efforts. In addition, the existence of Baitul Maal As'adiyah is able to minimize the space for the role of loan sharks whose existence is very detrimental to small businesses.